Identifikasi Jenis Bintang Laut di Pantai Awang Kabupaten Lombok Tengah - Hariyati, Astri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Sea stars are one of the echinoderms, members of the Asteroidea class. In aquatic animal ecosystems, echinoderms have very important value as environmental cleaners in the sea, such as eating carcasses and animal waste under the sea. This research aims to identify the types of starfish found in the waters of Awang Beach, Awang Hamlet, Mertak Village, Pujut District, Central Lombok Regency. This type of research is exploratory descriptive research. This research uses a purposive sampling method with three stations, each station consisting of 4 plots. Based on the results of the data analysis that was carried out, three types of starfish were obtained at Awang Beach, namely Protoreaster nodosus, Archaster typichus, and Linckia laevigata.